ANALYSIS OF THE INFLUENCE OF TIKTOK SHOP'S ONLINE MARKETING STRATEGY ON CONSUMER PURCHASING DECISIONS ON MS GLOW PRODUCTS - Alfatjil Defni Hasanah; Juwita; Nur Mismeitha Arielyan (Yayasan Wayan Marwan Pulungan, 2025)
This study aims to analyze the impact of online marketing strategies through TikTok Shop on consumer purchasing decisions for MS GLOW products. With the increasing use of social media platforms in marketing, TikTok Shop has emerged as an effective channel for reaching consumers, particularly among the younger generation. The research method employed is library research, which involves collecting and analyzing various literature, articles, and previous studies related to digital marketing and consumer behavior. The findings indicate that the marketing strategies implemented on TikTok Shop, such as creative content, direct interaction with consumers, and the use of influencers, have a significant impact on purchasing decisions. Additionally, factors such as brand trust, product quality, and user experience also play a crucial role in influencing consumer decisions. This research is expected to provide insights for marketers and business practitioners in formulating more effective marketing strategies in the digital era.